A marine reservoir correction for the Houtman-Abrolhos Archipelago, East Indian Ocean, Western Australia - Squire, Peter; Joannes-Boyau, Renaud; Scheffers, Anja; Nothdurft, Luke; Hua, Quan; Collins, Lindsay; Scheffers, Sander; Zhao, Jian-Xin (Department of Geosciences, University of Arizona, 2013)
High-precision analysis using accelerator mass spectrometry (AMS) was performed upon known-age Holocene and modern, pre-bomb coral samples to generate a marine reservoir age correction value (ΔR) for the Houtman-Abrolhos Archipelago (28.7°S, 113.8°E) off the Western Australian coast. The mean ΔR value calculated for the Abrolhos Islands, 54 ± 30 yr (1σ) agrees well with regional ΔR values for Leeuwin Current source waters (N-NW Australia-Java) of 60 ± 38 yr. The Abrolhos Islands show little variation with ΔR values of the northwestern and north Australian coast, underlining the dominance of the more equilibrated western Pacific-derived waters of the Leeuwin Current over local upwelling. The Abrolhos Islands ΔR values have remained stable over the last 2896 cal yr BP, being also attributed to the Leeuwin Current and the El Niño Southern Oscillation (ENSO) signal during this period. Expected future trends will be a strengthening of the teleconnection of the Abrolhos Islands to the climatic patterns of the equatorial Pacific via enhanced ENSO and global warming activity strengthening the Leeuwin Current. The possible effect upon the trend of future ΔR values may be to maintain similar values and an increase in stability. However, warming trends of global climate change may cause increasing dissimilarity of ΔR values due to the effects of increasing heat stress upon lower-latitude coral communities.